Runoff and discharge pathways of microplastics into freshwater ecosystems: A systematic review and meta-analysis - J. Wang; K. Bucci; P.A. Helm; T. Hoellein; M.J. Hoffman; R. Rooney; C.M. Rochman (Canadian Science Publishing, 2022)
Although many studies have focused on the importance of littering and (or) illegal dumping as a source of plastic pollution to freshwater, other relevant pathways should be considered, including wastewater, stormwater runoff, industrial effluent/runoff, and agricultural runoff. Here, we conducted a meta-analysis focused on these four pathways. We quantified the number of studies, amount and characteristics of microplastics reported, and the methods used to sample and measure microplastics from each pathway. Overall, we found 121 studies relevant to our criteria, published from 2014 to 2020. Of these, 54 (45%) quantified and characterized microplastics in discharge pathways. Although most focused on wastewater treatment plant effluent (85%), microplastic concentrations were highest in stormwater runoff (0.009 to 3862 particles/L). Morphologies of particles varied among pathways and sampling methods. For example, stormwater runoff was the only pathway with rubbery particles. When assessing methods, our analysis suggested that water filtered through a finer (<200 um) mesh and of a smaller volume (e.g., 6 L) captured more particles, and with a slightly greater morphological diversity. Overall, our meta-analysis suggested that all four pathways bring microplastics into freshwater ecosystems, and further research is necessary to inform the best methods for monitoring and to better understand hydrologic patterns that can inform local mitigation.